Studi Analisa Ontologi, Epistemologi dan Aksiologi dalam Filsafat Pendidikan Islam di SMP Muhammadiyah 1 Kudus - Mujiburrohman, Mujiburrohman; Amriati, Ulil (TSAQOFAH, 2026)
Islamic educational philosophy functions as a conceptual and normative foundation for the implementation of Islamic education, directing all educational processes toward the goal of forming morally upright individuals. This study aimed to analyze the ontological, epistemological, and axiological dimensions of Islamic educational philosophy and their implementation in educational practice at SMP Muhammadiyah 1 Kudus. A qualitative approach with a philosophical–empirical design was employed, with data obtained through in-depth interviews with Islamic Religious Education teachers, general subject teachers, and the vice principal for curriculum affairs, supported by institutional documentation. The findings showed that, ontologically, teachers view students as creatures of Allah who possess physical and spiritual potential that must be developed in a balanced manner; epistemologically, the learning process integrates sources of knowledge in the form of revelation, reason, and empirical experience; and axiologically, education is directed toward the formation of noble character, Islamic values, and the beneficial application of knowledge in social life. These findings affirm that Islamic educational philosophy does not remain at the conceptual level, but is concretely implemented in the planning and implementation of teaching and learning at school. This study contributes to strengthening the discourse on Islamic educational philosophy grounded in institutional practice and offers an empirical depiction of how these philosophical foundations are operationalized in the context of Islamic secondary education.